EUTHANASIA DALAM ISLAM: ANALISIS FIQH DAN HUKUM POSITIF DI INDONESIA - Susanti, Maria (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
Euthanasia is the act or practice of killing or permitting the death of hopelessly sick or injured individuals in a relatively painless way. This is one of the issues being debated scholars, intellectuals as well as the medical community. This can be excutedfor reason of mercy. Therefore, euthanasia closelyrelates with the right to die or right to death of a patient. There are a lot of reasons for people do euthanasia generaly, it is done because the suffering of a patient before the death phase so the idea to excute euthanasia is deliberately can free the patient. In Indonesia, it has a legal effort associated with euthanasia include the people who helps the action and its equipment. It has been arranged. Likewise, Islam religion teaches to keep religion, soul, mind, offspring and property. The practice of euthanasia is included murder and forbidden by both criminal law and positive Islamic law.